2014
DOI: 10.1007/s11095-014-1324-4
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Enhancing Macromolecule Transport Through Paracellular Spaces Induced by Poly-L-Arginine: Poly-L-Arginine Induces the Internalization of Tight Junction Proteins via Clathrin-Mediated Endocytosis

Abstract: PLA induced the transient internalization of TJ proteins in cell-cell junctions via clathrin-mediated endocytosis, subsequently increasing the permeability of the Caco-2 cell monolayer to FD-4 via a paracellular route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…TJ proteins accumulate in early endosomes as a first station after internalization. Several reports indicate that claudin‐1, claudin‐5, claudin‐16, occludin, JAM‐A, and ZO‐1 accumulate in early endosomes in both epithelial and endothelial cells . Their presence in early endosomes is closely associated with diminished barrier function (hyperpermeability) .…”
Section: Early Endosomes: a Center Of Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…TJ proteins accumulate in early endosomes as a first station after internalization. Several reports indicate that claudin‐1, claudin‐5, claudin‐16, occludin, JAM‐A, and ZO‐1 accumulate in early endosomes in both epithelial and endothelial cells . Their presence in early endosomes is closely associated with diminished barrier function (hyperpermeability) .…”
Section: Early Endosomes: a Center Of Sortingmentioning
confidence: 99%
“…Several reports indicate that claudin-1, claudin-5, claudin-16, occludin, JAM-A, and ZO-1 accumulate in early endosomes in both epithelial and endothelial cells. 23,25,32,40,48,[68][69][70][71] Their presence in early endosomes is closely associated with diminished barrier function (hyperpermeability). 32,40,47,71 Furthermore, Rab5A depletion using small interfering RNA (siRNA) increased claudin-1 association with the plasma membrane in the human endothelial cell line EA hy.926 and also stabilized brain endothelial barrier function owing to an inability to further process internalized junction proteins.…”
Section: Endocytic Trafficking and Sorting Of Tj Proteinsmentioning
confidence: 99%
“…22) Caco-2 cell sheets were washed with HBSS, and the DMEM culture medium was replaced with HBSS. The test solutions containing polycations (PLO and PEG-PLO at various concentrations) and FD-4 (1.0 mg/mL) were applied to the apical side of the cell sheet.…”
Section: Fd-4 Permeation Experimentsmentioning
confidence: 99%
“…Therefore, it seems that nasal rhGH absorption is increased by increasing the solubility and the paracellular permeability of rhGH by PLA as the same mechanism identified previously. [13][14][15][16][17] With regard to the effects of the molecular weight of PLA, a delay in the rhGH absorption was observed with an increase in the molecular weight. In particular, T max in 1.0 % (w/v) PLA (150) was 9.6 h, and the rhGH absorption was remarkably delayed compared with that in the solutions with other concentrations and molecular weights of PLA.…”
Section: Discussionmentioning
confidence: 99%
“…11,13) In the studies on the mechanism of enhanced absorption by PLA in the mucosa, it has been found that PLA induces the enhanced paracellular permeability by the dispersion of tight junction proteins (claudin-4, occludin, zonula occludens-1 (ZO-1) and tricellulin) into the cytoplasm through the cell-cell junction. [14][15][16][17] In particular, it was known that occludin was important for macromolecular permeation among tight junction proteins. 18,19) In addition, it has been also demonstrated that adherens junction protein (E-cadherin, β-catenin) is dispersed by PLA from the cell-cell junction.…”
mentioning
confidence: 99%